Philippine agenda (GMA News and Public Affairs, 2007)
The five pillars of GMA news and public affairs, Mike Enriquez, Mel Tiangco, Jessica Soho, Arnold Clavio and Vicky Morales join forces in the groundbreaking pre-election series Philippine agenda. Combining the efforts GMA Networks multi-awarded news and public affairs teams, Philippine Agenda presents the country's biggest issues, education, health, corruption, housing, labor, hunger, crime and justice, and electoral reform with the objective of calling viewers to action.